Transformational Leadership, Organizational Climate, Job Satisfaction on Team Performance over Retail Store - Yonatan Setiadi; Rhian Indradewa; Tantri Yanuar Rahmat Syah (Journal of Multidisciplinary Academic, 2020)
This study aims to analyze the role of transformational leadership and its relationship with organizational climate, job satisfaction, and team performance. Here, the empirical study was conducted with a questionnaire applied to a sample of 170 team work leaders from Indonesian companies that are members of the retail store sector. The hypothesis was tested by Structural Equation Modeling (SEM) with the Lisrel program used in this study. The results showed that transformational leadership had a positive effect on job satisfaction and organizational climate on work teams. It was also found that job satisfaction has a positive influence on organizational climate, and the two constructs positively affect team performance. This study analyzes the strategic role of transformational leadership in organizational outcomes derived from teamwork to the extent that such leadership styles promote a positive organizational climate and a high level of employee satisfaction. Organizations can improve their performance through practices that promote this leadership style in their managers. This study extends the literature on transformational leadership by presenting empirical evidence on the relationship between leadership style, organizational climate, job satisfaction, and team performance in the specific context of an emerging economy such as Indonesia.